Some aspects of the theory of dynamical systems: a tribute to Jean-Christophe Yoccoz - Crovisier, Sylvain; Krikoria, Raphael; Matheus, Carlos; Senti, Samuel (Paris: Societe Mathematique De France, 2020)
This is the first two volumes which celebrate the memory of Jean-Christophe Yoccoz. These volumes present research articles on various aspects of the theory of dynamical systems and related topics that were dear to him.
V 1.
Includes bibliographical references
Keywords: Anealed Limit Theorems; Dynamical Systems